2014
DOI: 10.1016/j.ijid.2014.03.1389
|View full text |Cite
|
Sign up to set email alerts
|

Sexually transmitted bacterial infections among young women in Central Western Brazil

Abstract: We observed a high prevalence of chlamydial infection and sexual risk behaviors in this population. These findings are important to guide screening strategies in Brazil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
0
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 20 publications
4
27
0
9
Order By: Relevance
“…Similar evidence has been found in other studies [54, 55]. In our multivariate analysis, married women were 60% less likely to be at risk of STIs as compared to single women (OR = 0.4).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similar evidence has been found in other studies [54, 55]. In our multivariate analysis, married women were 60% less likely to be at risk of STIs as compared to single women (OR = 0.4).…”
Section: Discussionsupporting
confidence: 91%
“…Our findings were consistent with other studies which reported that sexual activity with many partners increases the odds of STIs [53, 54]. However, the association was not statistically significant in our study following adjustment for all possible confounding factors (age, marital status, level of education, occupation, history of pregnancy, age at first sex, history of STIs, STIs treated in the past 12 months, and HIV status), which negatively confounded this relationship.…”
Section: Discussionsupporting
confidence: 90%
“…Chlamydia trachomatis causes long term complications such as pelvic inflammatory disease, chronic pelvic pain, ectopic pregnancy, and infertility (4). Gonorrhea is an infection due to Neisseria gonorrhoeae and usually involves mucosa of the cervix, urethra, endocervix, fallopian tubes, rectum, and throat (5, 6). Generally clinical symptoms for gonorrhoeae are not different from genital chlamydial infection and clinically are indistinguishable (4).…”
Section: Introductionmentioning
confidence: 99%
“…No Brasil, a prevalência de infecções por C. trachomatis varia entre 4,3% e 31,0%, conforme estudos de base populacional/comunitária de grandes centros urbanos e estudos de base clínica, realizados com participantes frequentadoras de ambulatórios e clínicas ginecológicas 10,11,12,13,14,15,16,17,18,19 . Nas comunidades amazônicas, há escassez de conhecimento sobre a epidemiologia da infecção endocervical por C. trachomatis, o que impossibilita a criação de diretrizes que estabeleçam o rastreio e controle dessa infecção.…”
Section: Introductionunclassified